Psycho-cognitive assessment and quality of life in older adults with chronic obstructive pulmonary disease-carrying the rs4713916 gene polymorphism (G/A) of gene FKBP5 and response to pulmonary rehabilitation: a proof of concept study. (31st January 2022) - Marcolongo, Federica; Scarlata, Simone; Tomino, Carlo; De Dominicis, Chiara; Giacconi, Robertina; Malavolta, Marco; Bonassi, Stefano; Russo, Patrizia; Prinzi, Giulia
Abstract : Purpose: Chronic obstructive pulmonary disease (COPD) is characterized by pulmonary and extra-pulmonary multi-morbidity including depression, anxiety and cognitive disorders. Several studies investigated the association of the FKBP5 gene polymorphisms with susceptibility to anxiety, depression, and behavioral disorders. The FKBP5 gene codifies the FKBP51 protein which modulates the glucocorticoid receptor in the adaptive stress response. Genetic variants of the FKBP5 gene have been associated to a higher risk of developing mental disorders. We analyzed the association of genetic variants and stress exposure investigating the susceptibility to psychological distress and the impact on cognitive balance and quality of life (QoL) of COPD patients carrying the rs4713916 polymorphism (G/A) and we examined its association, with COPD rehabilitative outcomes. Materials and methods: A pilot study evaluated cognitive, psychological, clinical alterations/disorders, QoL, and coping strategies in 70 older adults with COPD, undergoing pulmonary rehabilitation, stratified according to the FKBP5 rs4713916 genotype (GG or GA). Results: Carriers of rs4713916 polymorphisms (G/A) show better cognitive performances, a higher degree of independence in the daily living activities, better QoL, no presence of depressive mood and anxiety symptoms, no family history of psychiatric disorders, more ability to cope with stressors by avoiding emotions but demanding emotional support, and lesser use of anti-anxiety, anti-depressant, anti-psychotic, hypnotic-sedative drugs. No difference was found in the number of comorbidities. Conclusion: These results offer valuable insights into the role of FKBP5 in the complex network of mechanisms associated to clinical, psychological and behavioral features of COPD patients.